Tracking and Size Estimation of Objects in Motion based on Median of Localized Thresholding - Gujjunoori, Sagar; Oruganti, Madhu; Aparna, N.; Srija, M.; Dangare, Chaitrali (International Journal of Engineering and Technology, 2018)
Motion detection and tracking play an important role in Computer vision and Robotics. Optical flow based methods to estimate the motion are widely explored during the last decade. The motion information retrieved from these techniques has enormous applications. Video analysis based on the size, speed, and directions of objects have wider applications in computer vision, robotics and watermarking. Segmentation of moving objects based on the optical flow is very challenging. In this paper, we present a model to estimate the size of a moving object based on the optical flow technique and present localized thresholding technique. Over segmentation is reduced by the proposed local thresholding technique and use of bilateral filtering. We compare our results with Sagar et al. scheme. Â Â